Biceps and Rotator Interval: Imaging Update - Beltran, Luis S.; Beltran, Javier (Seminars in Musculoskeletal Radiology, 2014)
The rotator interval contains several important anatomical structures that contribute to the stability and normal function of the shoulder joint including the biceps tendon, coracohumeral ligament, superior glenohumeral ligament, rotator interval capsule, anterior fibers of the supraspinatus tendon, and superior fibers of the subscapularis tendon. Rotator interval pathology is associated with biceps instability, glenohumeral instability, and adhesive capsulitis, all of which can be challenging to clinically diagnose and treat. The complex anatomy and orientation of the rotator interval structures within a relatively small space can make it difficult to evaluate by imaging; however, improvements in MR technology have allowed better detection of disease in this region. Furthermore, the rotator interval is not routinely evaluated arthroscopically unless the clinical examination or imaging findings suggest pathology at this level. Imaging, therefore, can play a significant role in helping the clinician make the diagnosis and initiate appropriate treatment. This article discusses the normal anatomy and biomechanics of the rotator interval and its structures as well as the normal and pathologic appearances on imaging and the treatment options of abnormalities of structures in this region.
Keywords: rotator interval; biceps tendon; MR imaging; anatomy; pathology